Knowing is not enough: Awareness, Practice Gaps in Cervical Cancer Screening in Young Women - Jabeen, Musarrat; Saba, Naseem; Zuhra, Hina; Rauf, Isma; Samreen Hamid, Beenish; Khan, Fareeha (Journal of Neonatal Surgery, 2025)
Background: Cervical cancer is one of the causes of morbidity related to cancer in low-resource environments in women. Even though there are good screening strategies, their use among young women is low. Objective: To assess awareness, screening practices, and the gap between knowledge and behavior regarding cervical cancer screening among young women. Methodology: The study was a descriptive cross-sectional study undertaken between January 2023 and January 2024 in District Women Hospital MTI DIKHAN and Liaquat Memorial Hospital Kohat. Convenience sampling was applied to enroll 62 women between the ages of 18-29 years. The information was gathered by way of structured interviews. Descriptive statistics was used to analyze knowledge and screening practices and chi-square test was used to test associations. Results: Majority of the respondents (90.3) had heard of cervical cancer and 79.0% had heard about Pap smear test. Nevertheless, only one out of five had ever been screened (17.7). Good knowledge was highly related with an increased screening intake (p = 0.002). Absence of symptoms and information on screening facilities were the most prevalent impediments to screening. Conclusion: Despite high awareness, cervical cancer screening uptake among young women was low. Focused educational interventions and improved access to screening services are needed to convert awareness into preventive action